An analysis of road accidents caused by the current road infrastructure in Romania - Gheorghe Neamțu; Marinela Ință (Journal of Research and Innovation for Sustainable Society)
The scientific paper presents in a concrete and elegant way an analysis of how the poor quality and insufficiency of the current road infrastructure in Romania negatively influences road safety. The existing road infrastructure in our country is built and developed on the basis of roads built in the 1950s and 1960s, largely modernised, but still insufficient in terms of high speed roads. Specialists in the field consider that average traffic speeds on the existing road infrastructure at that time are largely influenced by a number of factors that are exclusively related to it. A high density of localities and the roads that cross them, the topography, the climate, traffic jams, the defective way of action of the authorities, sometimes the lack of horizontal and vertical signalization, the obstacles encountered at every turn, the non-conforming, undersized design or construction of traffic lanes and other elements of infrastructure, current legislation with many interpretations, heavy, heterogeneous and congested traffic, all of which make traffic participants unsafe and stressful and generate serious road events or accidents, resulting in human casualties and significant material damage. At national level, these are just a few of the most important issues negatively affecting infrastructure. In order to remove these negative, nonconforming aspects, which do not add value to the modern society it serves, it is imperative that major investments are undertaken in a relatively short time to develop a modern, sustainable and durable road infrastructure. In this way, those interested can find out the current state of research in the field, as well as data and figures on the number of road accident fatalities caused by the poor state of road infrastructure in Romania. The road safety management carried out on the current road infrastructure and the degree of sustainability provided by the authorities is then presented. At the end of the paper, conclusions in the field are presented.